2020
DOI: 10.1051/e3sconf/202015705011
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter Wave Radar for Intelligent Transportation Systems: a Case Study of Multi-Target Problem Solution

Abstract: The influence of millimeter-wave radar receiver noise on the probability of unambiguous determination of unmanned vehicles speed and range in the intelligent transportation system of the «smart city» is investigated. For the proposed new multi-target detection method for FMCW radar, the effect of the technical parameters of the vehicle radars on the required signal-to-noise ratio (SNR) of the receiver is estimated to ensure the probability of true determination of target parameters at 98%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A linear frequency-modulated microwave radar waveform is used in many applications, including microwave-range automobile radars for the simultaneous measurement of velocity and distance, which use signals of a special shape, including frequency-modulated continuous-wave (FMCW) [ 51 ]. Mathematical models of the received microwave signal for automotive radar systems taking into account a different range of velocity and distance for vehicles, were proposed in [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. In [ 52 ], it is shown that the use of phase methods to determine the speed of the target significantly reduces the noise immunity of the radar, and methods based on processing the amplitude spectrum of the received radio signal by the Fast Fourier Transformation (FFT) are therefore preferable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A linear frequency-modulated microwave radar waveform is used in many applications, including microwave-range automobile radars for the simultaneous measurement of velocity and distance, which use signals of a special shape, including frequency-modulated continuous-wave (FMCW) [ 51 ]. Mathematical models of the received microwave signal for automotive radar systems taking into account a different range of velocity and distance for vehicles, were proposed in [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. In [ 52 ], it is shown that the use of phase methods to determine the speed of the target significantly reduces the noise immunity of the radar, and methods based on processing the amplitude spectrum of the received radio signal by the Fast Fourier Transformation (FFT) are therefore preferable.…”
Section: Introductionmentioning
confidence: 99%
“…Using a computer experiment in LabVIEW (Laboratory Virtual Instrumentation Engineering Workbench), the probability of the unmanned vehicles’ true parameters determination at various ratios of the signal to noise at the input of the radar receiver in multi-target mode was investigated. The influence of millimeter-wave radar receiver noise on the probability of unambiguous determination of unmanned vehicles’ speed and range in the intelligent transportation system of the “smart city” is investigated in [ 58 ]. For the proposed new multi-target detection method for FMCW radar, the effect of the technical parameters of the vehicle radars on the required signal-to-noise ratio (SNR) of the receiver is estimated to ensure the probability of true determination of target parameters at 98%.…”
Section: Introductionmentioning
confidence: 99%
“…A significant disadvantage of the method is the appearance of false radar targets (false alarms) [ 12 ]. One of the ways to combat false targets is the use of a segmented structure of a sounding radio signal with variable modulation parameters: chirp duration, frequency deviation and initial generation frequency [ 13 , 14 , 15 , 16 , 17 ]. The creation of a segmented structure of the sounding radio signal can significantly reduce the likelihood of false targets.…”
Section: Introductionmentioning
confidence: 99%